Development of CBCT system for medical-physics laboratory improvement. (June 2020) - Susilo,; Darsono, T; Setiawan, R; Taufiq, U A; Yulianti, I; Fianti,
Abstract: Films used in Rontgen aperture by conventional radiography process yielding a fluorescent-based digital radiography have been conducted in medical-physics laboratory, Unnes for several applications. The continued research was improving the 2D radiograph imaging to be 3D, i.e. the object was rotated and X-Ray radiated simultaneously that yielded a 2D radiograph data by reconstruction and rendering. These covered a development of simulation object, an algorithmic modeling of scanning simulation and FDK (Feldkamp, Davis, Kress), and finally utilizing the algorithms resulting in 3D radiograph. In the future, this cheap technology would be a benefit in dentistry, because this technology is not popular nowadays, an implication of the expensive cost. The development process covered; software developing stage of CBCT (cone beam computed tomography) system in Phantom, data analysis, and finally reaching the result: CBCT model in laboratory scale. Prototype development of CBCT system can be done through study of the system in laboratory scale and then integrating the CBCT system for validated system in laboratory scale. According to the background above, we need innovation in CBCT system supporting the development of CBCT system aperture that leads to ease the dental implant installation in dentistry. At this level, CBCT prototype was used in early validation of the concept of CBCT technology in limit quantity and laboratory scale.